Gut Hormones and Inflammatory Bowel Disease - Jonathan Weng; Chunmin C. Lo (Biomolecules)
Obesity-driven inflammation disrupts gut barrier integrity and promotes inflammatory bowel disease (IBD). Emerging evidence highlights gut hormones—including glucagon-like peptide-1 (GLP-1), glucagon-like peptide-2 (GLP-2), glucose-dependent insulinotropic polypeptide (GIP), peptide YY (PYY), cholecystokinin (CCK), and apolipoprotein A4 (APOA4)—as key regulators of metabolism and mucosal immunity. This review outlines known mechanisms and explores therapeutic prospects in IBD. GLP-1 improves glycemic control, induces weight loss, and preserves intestinal barrier function, while GLP-2 enhances epithelial repair and reduces pro-inflammatory cytokine expression in animal models of colitis. GIP facilitates lipid clearance, enhances insulin sensitivity, and limits systemic inflammation. PYY and CCK slow gastric emptying, suppress appetite, and attenuate colonic inflammation via neural pathways. APOA4 regulates lipid transport, increases energy expenditure, and exerts antioxidant and anti-inflammatory effects that alleviate experimental colitis. Synergistic interactions—such as GLP-1/PYY co-administration, PYY-stimulated APOA4 production, and APOA4-enhanced CCK activity—suggest that multi-hormone combinations may offer amplified therapeutic benefits. While preclinical data are promising, clinical evidence supporting gut hormone therapies in IBD remains limited. Dual GIP/GLP-1 receptor agonists improve metabolic and inflammatory parameters, but in clinical use, they are associated with gastrointestinal side effects that warrant further investigation. Future research should evaluate combination therapies in preclinical IBD models, elucidate shared neural and receptor-mediated pathways, and define optimal strategies for applying gut hormone synergy in human IBD. These efforts may uncover safer, metabolically tailored treatments for IBD, particularly in patients with coexisting obesity or metabolic dysfunction.